Drivers of Antarctic sea ice volume change in CMIP5 models - Schroeter, S; Hobbs, W; Bindoff, NL; Massom, R; Matear, R (Journal of Geophysical Research: Oceans, 2018)
Antarctic sea ice trends have to date been linked to surface winds, through sea ice motion and atmospheric thermal advection. This paper analyzes sea ice volume in 10 CMIP5 model configurations under pre-industrial and historical climate forcings, to compare the relative importance of ice motion and thermodynamic processes. We find that the models responses to historical forcings is dependent on their sea ice motion formulation; models with low-magnitude sea ice motion tend to have historical trends that are dominated by thermodynamic processes, whilst sea ice models with higher-magnitude motion have more spatially variable relative contributions from dynamic and thermodynamic processes. Trends at the sea ice edge during the season of sea ice advance are generally dominated by dynamic processes, whereas during retreat thermodynamic trends dominate. The models show more disagreement in the sea ice interior. This analysis highlights the different estimates and patterns of sea ice volume among global climate models and offers insight into the drivers of sea ice volume change as well as the subsequent implications for simulated atmosphere-sea ice-ocean interactions.